ANALISIS FAKTOR USIA, PENDIDIKAN, PARITAS DAN JENIS PERSALINAN TERHADAP KEBERHASILAN INISIASI MENYUSU DINI (IMD) - Yuniar Angelia Puspadewi (Media Husada Journal of Midwifery Science, 2024)
Breasfeeding Early Initiation is an activity of allowing a newborn baby to breastfeed immediately within the first hour of birth, along with contact between the baby's skin and the mother's skin. If IMD is not carried out in less than an hour or there is a fabric barrier between the baby's skin and the mother's skin so that they do not touch each other, then IMD is said to be imperfect. In Indonesia, this IMD policy has been socialized since August 2007. Nationally in 2021, the percentage of newborns within the first hour who have received IMD is 82.7%. The aim of this research is to determine the factors of age, education, parity and type of delivery on the success of IMD in TPMB Malang City. This type of research is quantitative with a cross sectional design. The total sample was 30 people who gave birth at TPMB or were referred to the hospital. Questionnaire was used to collect data. This research used chi-square test for bivariate and logistic regression for multivariate. The results showed a relationship between parity (p value 0.028 and OR 5.500) and delivery type (p value 0.040 and OR 9.333) on the success of IMD. There is no relationship between age (p value 0.674) and education (p value 1.000) on the success of IMD. The most influenced factor was the delivery type with an OR of 9.333, which means that normal birth had a success rate of IMD 9 times higher than those who give birth via caesarean section. Therefore, it is hoped that whatever type of birth will be carried out, you should still be able to carry out IMD.